'I can tell when you're staring at my glass …': self- or co-surveillance? Couples' management of risks related to alcohol use during pregnancy. (17th November 2019) - Hammer, Raphaël
Abstract : Social researchers have largely used the framework of self-surveillance to describe the experience of pregnant women within a social context characterised by risk avoidance for the sake of their baby. However, men's positions regarding the risk discourses surrounding alcohol use during pregnancy and their engagement in their partners' regulation of abstinence remain unclear. Using a socio-cultural approach to risk perception, this study contributes to the understanding of the lay management of health-related risk as a relational issue by considering the couple relationship as a significant context that shapes responses to risk in everyday life. In this article, I explore the woman's and her partner's management of the risks surrounding alcohol consumption during pregnancy. This study draws on joint interviews with 30 first-time expectant couples conducted in 2014 in Switzerland. I found that all the women's changes of their drinking had been their personal choice and had been seldom discussed with their partners. While women's responses to risk discourses reflected their engagement in self-surveillance, most of the men were actively involved in their partners' self-regulation, in terms of support for the transition to abstinence, endorsement of maternal responsibility, and monitoring the woman's behaviour. I show that the management of the risks related to alcohol consumption was a matter of co-surveillance, rather than of self-surveillance. Although co-surveillance was most often experienced as shared responsibility, some couples experienced conflicts that emphasised the moral meaning of risk related to alcohol consumption during pregnancy.